PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN MELALUI KUALITAS HUBUNGAN - EKO PRASTYO, DIAN (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: Company need transformational leader who is able to encourage his subordinates to always improve employee performance. Transformational leader must be able to establish a good relationship quality of the subordinates so that it will also be able to improve employee performance.This quantitative study takes the total sample of 34 employees of the South of Surabaya CS division PT. Telekomunikasi Indonesia by using sampling techniques saturated. The data analysis techniques using descriptive analysis that use the average statistical by category Three-box Method and inferential analysis using the Partial Least Square (PLS). The result show: (a) transformational leadership style affects employee performance significantly and positively (b) transformational leadership style affects relationship quality significantly and positively (c) relationships quality affects employee performance significantly and positively (d) relationship quality has a mediatorroleimpact of transformational leadership style on employee performance. Keywords: transformational leadership, relationship quality, employee performance.